IADC/SPE Asia Pacific Drilling Technology Conference and Exhibition 2008
DOI: 10.2118/114678-ms
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Formations Rendered Less Problematic with Solid Expandable Technology

Abstract: To reach drilling objectives in dynamic formations requires robust technology that can adapt to unpredictable wellbore conditions. Such is the case with operations in Asia Pacific; a very tectonically active region. The shifting plates put the earth's crust under extreme stress, which has a propensity to cause various difficult drilling conditions including:FaultsHigh pore pressureWellbore instability These issues are difficult to predict, both in occurrence and true vertical depth (TVD), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…One can also apply SET in fixing the aquifer casing leak with substantial savings [30]. Carlos et al [31] and Jennings [32] reported the application of SET in reducing the tapering effect that occurs when using multiple casing strings in deepwater drilling. These expandable systems conserve valuable hole size at total depth.…”
Section: Literature Reviewmentioning
confidence: 99%
“…One can also apply SET in fixing the aquifer casing leak with substantial savings [30]. Carlos et al [31] and Jennings [32] reported the application of SET in reducing the tapering effect that occurs when using multiple casing strings in deepwater drilling. These expandable systems conserve valuable hole size at total depth.…”
Section: Literature Reviewmentioning
confidence: 99%